Exercise performance is regulated during repeated sprints to limit the development of peripheral fatigue beyond a critical threshold - Hureau, Thomas J.; Olivier, Nicolas; Millet, Guillaume Y.; Meste, Olivier; Blain, Gregory M. (Experimental physiology, 2014)
New Findings What is the central question of this study? We asked whether exercise performance is regulated during all‐out repeated sprints (involving peak cycling‐specific muscle activation and limited pacing strategy) in order to restrain the total degree of peripheral fatigue development. What is the main finding and its importance? Our results showed that power output is adjusted during repeated sprints to limit the development of peripheral fatigue to a critical threshold, independently of the degree of pre‐existing fatigue. These findings emphasize the important role of peripheral fatigue in adjustment of power output during exercise. We hypothesized that exercise performance is adjusted during repeated sprints in order not to surpass a critical threshold of peripheral fatigue. Twelve men randomly performed three experimental sessions on different days, i.e. one single 10 s all‐out sprint and two trials of 10 × 10 s all‐out sprints with 30 s of passive recovery in between. One trial was performed in the unfatigued state (CTRL) and one following electrically induced quadriceps muscle fatigue (FTNMES). Peripheral fatigue was quantified by comparing pre‐ with postexercise changes in potentiated quadriceps twitch force (ΔQtw‐pot) evoked by supramaximal magnetic stimulation of the femoral nerve. Central fatigue was estimated by comparing pre‐ with postexercise voluntary activation of quadriceps motor units. The root mean square (RMS) of the vastus lateralis and vastus medialis EMG normalized to maximal M‐wave amplitude (RMS.Mmax−1) was also calculated during sprints. Compared with CTRL condition, pre‐existing quadriceps muscle fatigue in FTNMES (ΔQtw‐pot = −29 ± 4%) resulted in a significant (P < 0.05) reduction in power output (−4.0 ± 0.9%) associated with a reduction in RMS.Mmax−1. However, ΔQtw‐pot postsprints decreased by 51% in both conditions, indicating that the level of peripheral fatigue was identical and independent of the degree of pre‐existing fatigue. Our findings show that power output and cycling EMG are adjusted during exercise in order to limit the development of peripheral fatigue beyond a constant threshold. We hypothesize that the contribution of peripheral fatigue to exercise limitation involves a reduction in central motor drive in addition to the impairment in muscular function.